Housewife makes mouth-watering foods - Vashistha, Shasi (Indian Horticulture, 2019)
MRS Poonam Lata, a house-wife, has become a milestone in diversifying non-traditional commodities into value–added food products. She has become a source of inspiration to other villagers and farm woman due to her innovative art of adding recepies. The people in her village and surrounding rural areas have huge demand of her value-added mouth-watering products like mango panaa, badam sherbet, bajra laddu, bajra matar, dhlanch bajra etc. She earns about `10,000/- month and give employment to other women.